Patient satisfaction evaluation with the services in UiTM Vision Care Clinic / Nur Azlim Abdul Kasa - Abdul Kasa, Nur Azlim (2015)
The quality of health care services is extremely influences the compliance of patient with the treatment given by the healthcare provider. Thus, this study aimed at determining the level of patient satisfaction with the services in UiTM Vision Care Clinic in Universiti Teknologi MARA Puncak Alam Campus. A cross-sectional study involving 260 patients attending the clinic from March to April 2015 was carried out. They were selected through convenience sampling method. Using a set of questionnaire, the level of patient satisfaction was evaluated. The questionnaire was constructed based on several validated questionnaire with minimal modification. This questionnaire included five parts which were the demographic data, accessibility to the clinic, facility, quality of staff services and competency of examiner. A majority of the patients were generally satisfied with each subscale included in the questionnaire. A response of greater than 90% was satisfied with all the questions asked. There were some relationship shown between demographic data and independent variable (each subscale). There was no association between gender and each subscale. However, there was association between age and the satisfaction level of the location of the clinic (accessibility to the clinic subscale) with P =0.023 and also the professionalism of examiner (P=0.032). In addition, there was association between the educational level and friendliness of the staff with P =0.017 and with professionalism of examiner (P=0.045). Nevertheless, effective interventions was suggested towards improving the location problems will further increase patient satisfaction and hence the quality of services at UiTM Vision Care Clinic.